Pengaruh Inovasi Produk Terhadap Keputusan Pembelian Konsumen Pada Chicken Crush Tuasan: Studi Kasus Mahasiswa Program Studi Manajemen UNIMED - Arnol Wandra Zega; Nurul Wardani Lubis; Indah Monalisa; Jhon Kas Mote (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine and analyze the influence of innovation on consumer purchasing decisions for Chicken Crush Tuasan. The type of research used is quantitative research to measure consumer attitudes by distributing questionnaires. The sample in this research is students from the Management Study Program at Medan State University who have often consumed Chicken Crush Tuasan products, totaling 73 people. This research sample uses a data analysis tool in the form of IBM SPSS Statistics 25. The results of the research show that there is a positive and significant influence between Product Innovation and the Decision to Purchase Chicken Crush Tuasan as evidenced by the results of the coefficients table with Y = 13.885 + 0.734 with a significance value of 0.000 < 0.05, which means it has a positive and significant effect. Furthermore, based on the results in the Model Summary table, it was found that the result of R Square = 0.546, meaning that the contribution given by the Product Innovation variable (X) to Purchasing Decisions (Y) was 54.6%.